Моделювання процесу горизонтального узгодження рішень на підприємствах на основі рефлексивного підходу - Турлакова, С. С.; Логвіненко, Б. І.; Turlakova, S. S.; Lohvinenko, B. I. (Інститут економіки промисловості НАН України, 2021)
Обґрунтовано актуальність дослідження процесів узгодження рішень на підприємст-вах шляхом математичного моделювання відповідних процесів. Визначено поняття гори-зонтального узгодження рішень на підприємствах. Розглянуто моделювання процесу гори-зонтального узгодження рішень на підприємстві з наявністю координаційного центру на більш високому рівні,ніж той, де відбувається узгодження. Наведено два варіанти управ-ління процесом узгодження рішень на підприємствах із різними цілями координаційного центру. Перший передбачає досягнення мети управління координаційним центром, зацікав-ленимв одержанні достовірної інформації від агентів на рівні узгодження рішення, з вико-ристанням неманіпульованого прямого механізму. Другий ‒наявність упроцесі горизон-тального узгодження рішень на підприємстві у координаційного центру певної мети управ-ління. Рефлексивне управління в цьому випадку передбачає маніпулювання отриманням результату узгодження, який максимально буде наближений до деякого фіксованого зна-чення –мети управління координаційного центру.Застосування наведених моделей рефлексивного управління процесом горизонталь-ного узгодження рішень на підприємстві залежить від наявної мети управління у коорди-наційного центру. Використання відповідних моделей горизонтального узгодження на рів-нях управління сприятиме збільшенню оперативності процесів колективного прийняття рішень на підприємствах, що дозволить підвищити ефективність їх функціонування. Окреслено перспективний напрям дослідження –моделювання процесів узгодження рішень на різних рівнях управління.

The relevance of the study of the processes of coordination of decisions at enterprises by means of mathematical modeling of the corresponding processes has been substantiated in the pa-per. The concept of horizontal coordination of decisions at enterprises has been defined. The modeling of the process of horizontal coordination of decisions at an enterprise with the presence of a coordination center at a higher level than the one where the coordination takes place is con-sidered. At thesame time, two options for managing the process of coordinating decisions at en-terprises with different goals of the coordination center are given. The first case assumes the achievement of the goal of managing a focal point, interested in obtaining reliable information from agents at the level of decision coordination with an employment of a non-manipulated direct mechanism. The second case assumes that the coordination center has a specific management goal in the process of horizontal coordination of decisions at the enterprise. Reflexive control in this case provides for the manipulation of obtaining the result of agreement, which will be as close as possible to a certain fixed value –the control goal of the coordination center.The use of the models ofreflexive management of the process of horizontal coordination of decisions at the enterprise, which are given in the article, depends on the existing management goal of the coordination center. The use of appropriate models of horizontal coordination at man-agement levels will help to increase the efficiency of collective decision-making processes at en-terprises, which will improve the efficiency of their functioning. A promising direction of re-search has been defined –modeling the processes of coordinating decisions at different levels of management.
Modeling the process of horizontal coordination of decisions at enterprises based on a reflexive approach
Keywords: моделювання; процес узгодження; прийняття рішень; ефлексивний підхід; підприємство; modeling; coordination process; decision making; reflexive approach; enterprise